Nightwork [large type] - Roberts, Nora (Thorndike Press, a part of Gale, a Cengage company, 2022)
"Harry Booth started stealing at nine to keep a roof over his ailing mother's head, slipping into empty homes to find items he could trade for cash. When his mother finally succumbed to cancer, he left Chicago, but kept up his nightwork. Wandering from the Outer Banks to Savannah to New Orleans, he dons new identities and stays careful, observant, distant. He can't afford to attract attention or get attached. After Harry takes a job commissioned by Carter LaPorte, LaPorte decides he wants to own Harry. No matter what name he uses or where he goes, LaPorte casts a shadow over Harry's life. To truly free himself, he must face down his enemy once and for all"--